VRRAD-201 (INGR20032): First Ogura-CMS line of radish with sinuate leaf for hybrid development - Singh, BK; Singh, PM; Singh, B (Vegetable Science, 2021)
Radish (Raphanus sativus L., 2n=2x=18) belonging toBrassicaceae family is a most reliable year-roundvegetable crop grown worldwide for fleshy edible rootsand soft leaves. Genus Raphanus is a Greek word whichmeans ‘quickly appearing’ and representing to the quickgermination and fast-growing nature of the plants. Radishis an ancient crop, most probably native to the easternMediterranean and the Middle East where maximumdiversity prevails. However, central China, central Asiaand Hindustani center of origin appear to be secondarycenters where differing forms were evolved duringperiod of domestication. The ancient varieties were longand tapered rather than cylindrical, apically bulbous